Carbon market volatility analysis based on structural breaks: Evidence from EU-ETS and China - Yu, Haixu; Wang, He; Liang, Chuanyu; Liu, Zhaohua; Wang, Susheng (Frontiers in Environmental Science, 2022)
In recent years, carbon market transactions have become more active. The number of countries participating in carbon market regulation is increasing, and the carbon market's overall turnover continues to grow. It is important to study the features of carbon allowance price volatility for the stable development of the carbon market. This paper constructs a modified ICSS-GARCH model to analyze the volatility of carbon price returns and the dynamic characteristics of price fluctuations in the emissions trading system of the European Union (EU-ETS) and the Chinese carbon pilot markets in Hubei. The results show that fluctuations in carbon price returns have a leverage effect and that the impact of negative news on the market is stronger than that of positive news. The international climate and energy conferences, abnormal changes in traditional energy prices, and global public health emergencies all affect volatility and cause shocks to the carbon trading market. The modified ICSS-GARCH model with structural breaks can reduce the pseudovolatility of the return series to a certain extent and can improve the accuracy of the model. This research can give policymakers some implications about how to develop the carbon market and help market participants control the risks of fluctuations in carbon allowances. Regulators should enhance carbon price monitoring and focus on short-term shocks in the carbon market to reduce trading risks. The Chinese carbon market should strengthen the system design and develop carbon financial derivatives.